Social workers using sign language interpreters to ensure equitable services to the Deaf community - Koeras, Peter; Davids, Ronel Sanet (Social Work/Maatskaplike Werk, 2025)
Despite the recognition of sign language in South Africa, individuals who are Deaf face significant barriers, leading to stigmatisation and marginalisation. Social workers must be critically conscious of this and provide the necessary services to address these inequalities. Not all social workers are proficient in South African Sign Language to provide equitable services to the Deaf community and require the assistance of South African Sign Language Interpreters during social work micro interventions. However, there is limited literature on the experiences of social workers using these interpreters during this intervention. Seven social workers were selected to participate in a qualitative study using explorative descriptive research designs to understand the experiences of social workers using South African Sign Language Interpreters during micro-interventions. Non-probability purposive sampling was used with semi-structured interviews for data collection. The thematic analysis revealed three key themes: social workers’ feelings of helplessness, uncertainty, and emotional stress related to role clarity; challenges with inadequately trained SASL interpreters, interpretation accuracy, and rapport-building with clients; and enhancing services for individuals who are Deaf by incorporating culturally sensitive sign language training in higher education institutions to foster better relationships with SASL interpreters and clients.